Deciphering the unusual HLA‐A2/Melan‐A/MART‐1‐specific TCR repertoire in humans. Issue 9 (September 2014) - Romero, Pedro; Speiser, Daniel E.; Rufer, Nathalie
<x xml:space="preserve">Abstract</x> The Melan‐A/MART‐126‐35 antigenic peptide is one of the best studied human tumor‐associated antigens. It is expressed in healthy melanocytes and malignant melanoma and is recognized by CD8+ T cells in the context of the MHC class I molecule HLA‐A*0201. While an unusually large repertoire of CD8+ T cells specific for this antigen has been documented, the reasons for its generation have remained elusive. In this issue of the European Journal of Immunology, Pinto et al. [Eur. J. Immunol. 2014. 44: 2811–2821] uncover one important mechanism by comparing the thymic expression of the Melan‐A gene to that in the melanocyte lineage. This study shows that medullary thymic epithelial cells (mTECs) dominantly express a truncated Melan‐A transcript, the product of misinitiation of transcription. Consequently, the protein product in mTECs lacks the immunodominant epitope spanning residues 26–35, thus precluding central tolerance to this antigen. In contrast, melanocytes and melanoma tumor cells express almost exclusively the full‐length Melan‐A transcript, thus providing the target antigen for efficient recognition by HLA‐A2‐restricted CD8+ T cells. The frequency of these alternative gene transcription modes may be more common than previously appreciated and may represent an important factor modulating the efficiency of central tolerance induction in the thymus.